The New Challenge to Native Identity: An Essay on “Indigeneity” and “Whiteness” - Rebecca Tsosie (Washington University Journal of Law & Policy, 2005)
This Essay builds upon Cheryl Harris’s claim that “whiteness” is a form of “property” and suggests that the current challenges to Native “indigeneity” to the racial and cultural identity of Native peoples in recent years through various “special” legal rights. This Essay suggests that, with respect to indigenous peoples, the discourse of “whiteness” requires analysis within a global, as well as national context. This Essay examines four areas within which there is an active debate over “indigenous status”: political rights under international human rights law; cultural rights under international human rights law; rights to land and to ancestral human remains under domestic law; and rights to genetic resources. The root issue within each of these areas is who “owns” Native identity—political, cultural, ancestral, genetic—and what role does the concept of “indigeneity” play in these assertions of “ownership”? The Essay concludes by suggesting that Native cultural sovereignty, including tribal law and tribal epistemologies, will have an important role in asserting and maintaining Native rights to tangible and intangible tribal resources.
Keywords: Indians of North America; Critical race theory